Teacher Autonomy Perceptions of Iranian and Turkish EFL Teachers - KHEZERLOU, Ebrahim (Journal of History Culture and Art Research, 2013)
Abstract The study aimed at examining Iranian (N= 218) and Turkish (N=142) high school EFL teachers’ opinions about teacher autonomy over (a) the choice of appropriate teaching methods, strategies and techniques and implementation of the established curriculum (b) teacher involvement in decision making processes and (c) teachers’ use of personal initiative in solving their work problems. An 11-item questionnaire (Î±= .758) was used to measure autonomy perceptions of the participants. The results revealed that Turkish teachers’ autonomy perceptions were greater than that of Iranian teachers in the three teacher autonomy dimensions. Moreover, it was observed that male and master- holder teachers perceive less autonomy than female and bachelor-holder ones; whereas, no significant relationship were observed for the age and marital status variables with any teacher autonomy dimensions. Lastly, decision making dimension was the strongest predictor of teacher autonomy among both Iranian and Turkish teachers.